La morte di Socrate. Alcune riflessioni ricavate dall’Apologia di Platone - Pascual, L.C., Fernando (Alpha Omega, 2019)
Summary: The year 2001 recalls the 2400th. anniversary of the condemnation and execution of Socrates. This work tries to glean from Socrates’ Apology, written by Plato, elements constantly present in Western Thought. After some initial considerations about the Socratic question and the documental value of the Platonic story, three fundamental ideas are presented in Socrates’ defence: the search for truth, the enigma of death and the importance of the soul, considered as the “I” and its call to live in justice. These are central ideas in the whole of human Thought that cannot be forgotten in the millennium that begins. Parole chiave: Socrate, Platone, verità, sapere, morte, anima. Keywords: Socrates, Plato, truth, knowledge, death, soul.